Unframing the Black Diaries of Roger Casement - Mitchell, Angus (ABEI Journal, 2009)
For a century now, the disputed frontier region of the upper Amazon– bordering Brazil, Peru, Colombia and Bolivia – has been the subject for one of the most persistent controversies in Irish history. In 1910 and 1911 the British Consul, Roger Casement (1864-1916) undertook two separate voyages up the Amazon to investigate crimes against humanity: the decimation of people and environment resulting from the extractive rubber industry. These investigations ultimately helped the South American rubber boom go bust and persuaded international investors to switch interests to the new Anglo-Dutch rubber plantation economy of Southeast Asia. But since Casement’s execution in 1916 for his part in the Easter rising, a bitter controversy has raged over his reputationand the authenticity of the so-called Black Diaries. Three of these contested records configure with his Amazon voyages and are sources for analysing an important socio-economic tipping point in Latin American history. In 1997 & 2003 I edited two volumes of documents relevant to his Amazon investigations which formed part of an on-going methodological inquiry enabling a new and alternative textual reading of the Black Diaries and the re-evaluation of Casement as a critical voice in Irish and World history.1 The publication of these edited volumes reawakened a long-standing argument suggesting that the diaries areforgeries. In 2008 a comprehensive new biography was published on Roger Casement, which went to some length to discredit my nascent argument. This article is the first part of my response to the biographer, Séamas Ó Síocháin’s Roger Casement: Imperialist, Rebel, Revolutionary.